A STUDY ON STUDENT’S ADDICTIONS TO SOCIAL MEDIA - K N, Nagamani; M, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
One of the most important features of modern society is the growing impact of online communication tools, especially the internet. The main objective of this study is to examine the relationship of students with social media. Research Methodology: This is qualitative research. The scope of this study is limited to Kolar Gold Field students only. Conclusion: Nowadays students are more addicted to social media. Negative consequences like reduced productivity, depression, low self-esteem, stress, and low sleep quality. Hence it is recommended to students limit their social media usage and divert their minds toward other activities like playing games, reading books, and spending time with family and friends.